TOOLS, METHODS AND PRINCIPLES USED IN TEACHING THE OF JUMPING TECHNIQUE - Azizjon Yakubjonovich Shadiyev (Proximus Journal Publishing, 2024)
This article contains information aimed at studying the effectiveness of outdoor games in educating students of jumping ability and speed-strength qualities directly related to the formation of jumping skills at the initial stage of training in the support jump.
Keywords: technical and tactical endurance; agility; flexibility